The role of electronic word-of-mouth in consumers' online purchase decision making : an eye-tracking study - Jokinen, Joel (2016)
The aim of this study was to shed light on the consumers’ decision making processes in an online environment. The vast amount of information found online and the presence of online peer recommendations has shaped the purchase decision making environment – making it more simple in some situations, more complex in others. This study answers to the need for more research on consumers’ cognitive processes when making purchase decisions, the influence of website design factors towards consumer decision making as well as the social presence of others in online environments. Previously little research has been done on the effects of product ratings toward consumer attention through eye-tracking methodology. Eye-tracking methodology was chosen to overcome the limitations created by using solely self-report methods and projective techniques, such as surveys and interviews, in order to better understand the mental constructs and the behavior of a consumer. A 2 (decision complexity) X 2 (quality of product rating) between-subjects experiment design was employed for this study to assess whether consumers would try to ease cognitively demanding purchase decision making tasks through the use of social heuristics. The data (N=25) was collected through assessing the eye movements of multiple subjects. From the data eye-tracking parameters such as fixation duration, dwell time and the time to first fixation were analyzed through statistical tests. Supporting data was collected through asking the subjects for a brief verbalization of their thought process during the experiment. The results show a significant combined effect of task complexity and product ratings towards the decision making time. No significant combined effect of task complexity and product ratings was found for fixation duration, dwell time and the time to first fixation on the area of interest. A significant main effect was discovered between task complexity and dwell time percentage. Good product ratings were perceived faster than bad product ratings, which as a finding is in line with earlier research. Consumers also seem to be prone to using social heuristics, such as peer-made product ratings, to conform with others during the purchase decision making process, even if the purchase decision is seemingly simple.